2007
DOI: 10.1093/ndt/gfm079
|View full text |Cite
|
Sign up to set email alerts
|

Single UK centre experience on the treatment of PD peritonitis--antibiotic levels and outcomes

Abstract: We have confirmed that the International Society for Peritoneal Dialysis (ISPD) dosing guideline for vancomycin in CAPD and APD patients produces adequate serum concentrations of the antibiotics in the vast majority. However, large incremental dosing of vancomycin is needed if day-5 levels are low; especially for not-anuric patients. Whilst evidence of gentamicin toxicity in PD remains controversial, ISPD dosing regimen resulted in high levels for>50% patients. High gentamicin concentrations did not correlate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
3
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 17 publications
5
83
3
5
Order By: Relevance
“…An initial cure rate of 76.0% is similar to those reported in the literature (21,(23)(24)(25). Higher initial cure rates are reported in patients treated on an outpatient basis (19,20).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…An initial cure rate of 76.0% is similar to those reported in the literature (21,(23)(24)(25). Higher initial cure rates are reported in patients treated on an outpatient basis (19,20).…”
Section: Discussionsupporting
confidence: 88%
“…In other studies, although not always stated explicitly, most APD patients were switched to CAPD during peritonitis (21,22). Furthermore, adjustments for patient characteristics, such as age and gender, had not been made (23,24) or results were compared with historical data (20,25). Our retrospective study showed several differences in characteristics of our CAPD and APD populations.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-three per cent of patients in the present study and 31 -56% of patients from the study of Blunden et al (15) were reported to have serum gentamicin levels exceeding 2 mg/L, a threshold that has previously been associated with ototoxicity (9). However, no ototoxicity was observed in either investigation.…”
Section: Discussionsupporting
confidence: 41%
“…The uptake of vancomycin from normal peritoneal cavity is about 50%, which is enhanced up to 90% during episodes of peritonitis (9). Accepting the importance of saving residual renal function in peritoneal dialysis patients for longer times, the potential nephrotoxicity with aminoglycosides should taking in to accounts, although some studies did not demonstrate such results (10). In case of any allergy to cephalosporines, aztreonam is a good alternative.…”
Section: Treatmentmentioning
confidence: 99%